2015
DOI: 10.1590/0102-311x00077714
|View full text |Cite
|
Sign up to set email alerts
|

Time to death in a prospective cohort of 252 patients treated for fracture of the proximal femur in a major hospital in Portugal

Abstract: Time to death in a prospective cohort of 252 patients treated for fracture of the proximal femur in a major hospital in PortugalTempo até a morte após fratura do fêmur proximal: uma coorte prospectiva de 252 doentes tratados no segundo maior hospital em Portugal Tiempo transcurrido hasta la muerte después de una fractura de cadera: una cohorte prospectiva de 252 pacientes del segundo mayor hospital de Portugal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
6
0
6
Order By: Relevance
“…Thus, the finding that the risk of death is four times higher in patients with at least one type of comorbidity compared with those with no comorbidities is considered relevant, and it confirms data from Guerra et al, 13 who observed that the absence of comorbidities is associated with their so-called alive group, and that the presence of three comorbidities is associated with their so-called death group. The same occurs with Shebubakar et al 29 and with Campos et al, 30 who demonstrated that the presence of ≥ 2 comorbidities is associated with an increase in morbidity and mortality rates. Also regarding the choice for a purely quantitative analysis, we also consider that one of our goals was to create a line of reasoning that is reproducible and applicable to the general population, and not to specific groups and to their different levels of pathological involvement (patients with heart, coronary heart, liver disease, kidney or lung diseases, etc.).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, the finding that the risk of death is four times higher in patients with at least one type of comorbidity compared with those with no comorbidities is considered relevant, and it confirms data from Guerra et al, 13 who observed that the absence of comorbidities is associated with their so-called alive group, and that the presence of three comorbidities is associated with their so-called death group. The same occurs with Shebubakar et al 29 and with Campos et al, 30 who demonstrated that the presence of ≥ 2 comorbidities is associated with an increase in morbidity and mortality rates. Also regarding the choice for a purely quantitative analysis, we also consider that one of our goals was to create a line of reasoning that is reproducible and applicable to the general population, and not to specific groups and to their different levels of pathological involvement (patients with heart, coronary heart, liver disease, kidney or lung diseases, etc.).…”
Section: Discussionsupporting
confidence: 72%
“…Desta maneira, consideramos relevante o achado que demostra o risco de morte quatro vezes maior em pacientes com ao menos um tipo de comorbidade em comparação aos que não possuem comorbidades, corroborando Guerra et al, 13 que observou que a ausência de comorbidade é associada ao grupo de seu trabalho intitulado vivo e a presença de três comorbidades associada ao grupo intitulado óbito . O mesmo ocorre com Shebubakar et al 29 e Campos et al, 30 que demonstram que a presença de duas ou mais comorbidades está associada a um aumento da taxa de morbidade e mortalidade. Ainda no que diz respeito à escolha por uma análise puramente quantitativa, também levamos em consideração o fato de termos como objetivo a criação de uma linha de raciocínio reprodutível e aplicável à população de maneira geral e não a grupos específicos e seus distintos níveis de acometimento patológico (cardiopatas, coronariopatas, hepatopatas, nefropatas, pneumopatas, etc).…”
Section: Discussionunclassified
“…Even if stated by individual authors that no OA was observed when this last group was used as control, one cannot exclude both the influence of the fracture itself and the possible influence of concomitant milder undiagnosed forms of OA. Patients affected with proximal femur fractures are elderly subjects, which can be affected by milder forms of hip OA, with local and systemic biochemical changes before the time a radiological diagnosis of hip OA is made [ 42 ]. Also, fractures, due to the inherent aggression, are associated with both a local and a systemic biochemical response, with an increased inflammatory response [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, fractures, due to the inherent aggression, are associated with both a local and a systemic biochemical response, with an increased inflammatory response [ 43 ]. Both undiagnosed hip OA and the fracture-associated inflammatory reaction can lead to an underestimation of the neuroimmune activation in patients with hip OA, which represents an import bias in these comparisons [ 42 ]. Furthermore, it is known that expression of individual molecules changes along OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Older male patients with a lower cognitive status had a higher chance of developing postoperative delirium (Raspopovic et al). Campos et al (2015) examined the one year survival rate and mortality predictors in patients with fracture of the proximal femur. Survival was assessed at three, six, nine and 12 months after fracture and repair.…”
Section: Mortality Risk After Hip Fracturementioning
confidence: 99%